SIMULASI PEREDAMAN DISTORSI HARMONISA MENGGUNAKAN FILTER AKTIF DAN ANALISIS RUGI-RUGI DAYA PADA SISTEM KELISTRIKAN DI HOTEL THE BENE KUTA - I Nyoman Agus Sudiatma Pratama; I Wayan Rinas; Antonius Ibi Weking (Program Studi Teknik Elektro UNUD, 2017)
A non-linear load operation on a power system will generate harmonics. Operating non-linear loads on the simulated electrical system at the Bene Hotel Kuta created a harmonic current which resulted in power losses. In this study, the simulation used ETAP software, and determined the standard of THD (Total Harmonic Distortion) according to IEEE 519-2014, the standard maximum THDI value 5.0% and THDV maximum 5,0%. Compared the simulation results with the specified standards, installation of a high pass active filter, as well as power loss analysis before and after filter installation. THDI value of simulation result did not still meet the standard, with the average being 9.7%. The installation of a high pass active filter could reduce harmonic distortion with an average THDI value of 1.5% and a THDV value of 0.31%. The total power loss prior to installation of active filter was 153,119.8 Watt and after the installation it became 1,511.2 Watt. The decrease in filter values used 70% of the filter's maximum capability to obtain a more efficient filter, but it still met the specified THD standard. Total loss of power on electrical system was 11,885.5W.